The qur’anic exegesis as a medium of Islamic education in Indonesia: A discourse analysis of tafsir Rahmat by H. Oemar Bakry - Nasrul Fatah; Syarifah Laili; Muhammad Hafiz Saleh; Hidayatullah Ismail (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
This study aims to examine Tafsir Rahmat by H. Oemar Bakri as a representative work of the Nusantara exegetical tradition with a pedagogical orientation, functioning as a medium of Islamic education in the early twentieth century. The work emerged amid the dynamic efforts of Indonesian Muslims to balance the spirit of modernity with Islamic traditional values. Through communicative Malay and a simple interpretive style, Oemar Bakri presented tafsir as a means of da‘wah and moral education, particularly for the younger generation. Employing critical discourse analysis and contextual hermeneutics, this study explores the linguistic, ideological, and social dimensions embedded in the text. The findings reveal that Tafsir Rahmat not only interprets Qur’anic verses but also instills Islamic educational values emphasizing moral development, social responsibility, and religious character. Its pedagogical tone highlights the role of tafsir as a living educational discourse within the social and cultural context of Indonesian Muslim society.